Current Advances in the Genetic Basis of Rheumatoid Arthritis - Berrin Yüksel-Konuk,; Volkan Baltacı, (Archives of Rheumatology, 2009)
Rheumatoid arthritis (RA) is a heterogeneous and complex disease where both genetic and environmental risk factors are involved. Reviewing the increased familial incidence and increased disease susceptibility demonstrated in twin studies, RA clearly has a genetic component. More evidence for a strong inherited component in RA is supported by association studies of RA with variants in the human leukocyte antigen (HLA) region, particularly the HLA-DRB1 gene in a wide range of populations. After the discovery of HLA associations, traditional linkage and association studies have identified new RA risk loci. In the last few years, the demonstration of genetic associations through the use of genome-wide association studies (GWAS) with a technical capacity to genotype hundreds of thousands of single nucleotide polymorphisms (SNPs) in a cost-effective manner proceeded to uncover new RA susceptibility genes. We review herein recent progress made in the field of RA genetics. (Turk J Rheumatol 2009; 24: 218-21)